Propuesta Metodologica De Planificacion Para Ejecutar La Construcción De Terminales Terrestres Para Ciudades De 100.000 A 500.000 Habitantes - Viejo Alvarado, Miguel Antonio (2017)
The planning to execute a work constitutes an important stage in the process of construction of civil engineering works in particular in the execution of the construction of land terminals, since they have special characteristics in their construction process by the materials, equipment and facilities that the Integrated. In the execution of a work it is important to preset the details of the planning in order to expand and complement it, so that the construction processes do not undergo changes or alterations that result in the extension of deadlines and cost increases, a situation that is very frequently presented.